Pengaruh Rendahnya Minat Pemuda Bergabung dalam Organisasi Gerakan Pemuda Ansor di Desa Sukodono Kecamatan Karangrejo Kabupaten Tulungagung - Toriq, Mohammad Zuhril Syichona; Hasib, Mohammad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The low interest of youth in organisations can be caused by, among other factors, the internal lack of understanding of the role and benefits of organisations. The main objective of this research is to identify the factors that cause the low interest and analyse its impact on the dynamics and development of the organisation. The methodology used is descriptive qualitative research, with data collection through interviews and documentation. The results show that the low interest of youth is caused by several key factors: personal and psychological dimensions that tend to be individualistic and less comfortable with group social activities; economic and material factors due to the "profitoriented" orientation of youth who prioritise meeting financial needs; and social and environmental dimensions. The impact of this low interest can be seen in the stagnation of the regeneration process, which hinders the regeneration of the management and active members, as well as the dependence on the PAC for formal programme implementation. Nonetheless, Ansor Youth Movement has adapted through cultural and personal approach strategies, the use of social media, and the development of relevant participatory programmes. However, there are still gaps in communication effectiveness, unmet youth expectations of tangible benefits, and social barriers from the neighbourhood.